Nb-Doped MXene With Enhanced Energy Storage Capacity and Stability - Fatima, Mahjabeen; Fatheema, Jameela; Monir, Nasbah B.; Siddique, Ahmad Hassan; Khan, Bushra; Islam, Amjad; Akinwande, Deji; Rizwan, Syed (Frontiers in Chemistry, 2020)
MXenes presents unique materials for energy storage however, limited interlayer distance and structural stability with ongoing cycles limit their applications. Here, we have developed a unique method by incorporating Nb atoms to MXene (Ti3C2) to enhance its ability for higher ionic storage with longer stability. The computational analysis using density functional theory was made which explained material structure, electronic structure, band structure and density of states in atomistic detail. Nb-doped MXene showed a good charge storage capacity of 442F/g which shows application as a supercapacitor. The X-ray diffraction (XRD) indicated c-lattice parameter enhancement after Nb-doping in MXene (from 19.2A° to 23.4A°) which showed effect of induction of element with larger ionic radii (of Nb). Also, the bandgap changes from 0.9eV (for pristine MXene) to 0.1eV (for Nb-doped MXene) which gives signature of increased conductivity due to more metallic nature. In support of the experimental results. This work presents not only the effect of doping in MXene but also helps to understand the reasoning of the phenomena involved in changes in physical parameters that advances the field of energy storage based on 2D materials.